ANALISIS NORMATIF UNDANG-UNDANG NO. 1 TAHUN 2013 TENTANG LEMBAGA KEUANGAN MIKRO (LKM) ATAS STATUS BADAN HUKUM DAN PENGAWASAN BAITUL MAAL WAT TAMWIL (BMT) - Novita Dewi Masyithoh (Economica: Jurnal Ekonomi Islam, 2014)
Baitul Maal Wat Tamwil (BMT) has been growing rapidly in Indonesia from year to year. However, its development has still not been followed by the legal rules. Some of them follow the legal system of Cooperatives, that are Act No. 25 of 1992 and Decree of the Minister of Cooperatives and SMEs, No. 91 /KEP/M.KUKM/IX/2004 about the Implementation Guidelines for Cooperative Operations of Islamic Financial Services (KJKS). However, after Act No. 1 of 2013 about Micro-finance Institutions had been issued, the legal institutional status of BMT and its supervision has become a problem for the existence of BMT. Therefore, this study met the issues of how the legal status and supervision of BMT before and after the issued Act No. 1 of 2013 about micro-finance institutions.This study was an empirical law rechtdogmatik against Act No. 1 of 2013 about Micro-finance Institutions. It used primary legal materials, namely the Micro-finance Institutions Act; the result of interviews; and documentation that were analyzed qualitatively.The result analysis showed that before the Law of Microfinance Institutions was issued, there were 3 groups of BMT, namely: BMT with the Cooperative legal entity and being supervised by the State Ministry of Cooperatives and SMEs; BMT that were formed under the foundations legal entity; and BMT that were formed under Non Governmental Organisation. However, after Act No. 1 of 2013 had been issued, Microfinance Institutions should only have legal status, either as a cooperative or an incorporated company (PT). In addition, the supervision should be conducted by the Financial Services Authority of Indonesia (OJK) coordinated with both the Ministry of Cooperatives and SMEs, and the Ministry of Home Affairs. Nevertheless, the competence of supervision has still not been clearly regulated in the Microfinance Institutions Act, because the new law might effectively run two years after being enacted while the implemention is also still not regulated yet.Thus, it should be recommended to make clear implementation rules in the legal status of Microfinance Institutions, especially for those not have legal entities as well as those should transform. Similarly, in terms of supervision, there should be a clear competence of supervision performed by the FSA and the two mentioned Ministry above. So, there might not be either overlapping or loose supervision.